Медико-психологічні складові постковідного синдрому у пацієнтів, які перенесли гострі цереброваскулярні захворювання - Галанта, Юрій (Psychosomatic Medicine and General Practice, 2023)
Abstract Background Today, in clinical practice, the issue of providing psychological assistance to patients who have suffered acute cerebrovascular diseases and suffer from post-convulsive syndrome remains open. The practical problems of the medical and psychological service in neurology are the lack of a strategy of medical and psychological care, standards, protocols, targeted training of mental health specialists and medical workers in the field of medical psychology, coordination of psychological and medical services, practical measures aimed at increasing accessibility and bringing psychological care closer to patients. Methods To achieve the set goal and tasks, a number of medical and psychological methods were used to study cognitive functions, the psycho-emotional sphere, the level of daily activity, the degree of fatigue and the assessment of the quality of life. The results The study revealed moderate cognitive impairment in patients with post-covid symptoms, increased levels of anxiety and depression, increased levels of asthenia, increased levels of fatigue, and decreased levels of quality of life. At this stage of the study, the development of dementia processes in patients with post-covid symptoms was not detected. Conclusions In patients with post-covid symptoms, there is a moderate decrease in cognitive functions. An increased level of fatigue, asthenia, anxiety and depression are expressed. At this stage of the study, no dementia processes, as well as motor disability, were detected. Due to the occurrence of a number of negative symptoms, a significant decrease in the quality of life is observed.